INVESTIGATING THE USE OF EFL TEACHERS’ ORAL CORRECTIVE FEEDBACK IN SPEAKING CLASSES - Nadifa, Iva Dian (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
As far as making errors is unavoidable in speaking class, oral corrective feedback (OCF) plays a crucial role to solve that problem. For the past two decades, OCF has become the debatable issue among researchers. This present study was conducted in one of the English courses in East Java, Indonesia. The participants were one native teacher and one non-native teacher teaching two different classes alternately.  The speaking class was for elementary school students. This qualitative study has several aims; 1) to investigate the distribution of OCF types that providing by the teachers in the speaking class, 2) to know whether or not there is an ignorance of the errors by the teachers and the reason behind it, 3) the types of OCF that often used by the teachers. The data was collected through video recording, stimulated recall and semi-structured interview. The results evinced that the teachers provided all the types of OCF to the students with different portions of usage. Recast became the type of OCF that is commonly used by teachers. Furthermore, the teachers corrected almost of the student’s errors. Unfortunately, there several ones that ignored by them. The ignorance of the student’s error due to some reasons such as tiredness and lack of knowledge. Nevertheless, the most prominent reasons were they did not want interrupt the student’s utterances in order to not create the students’ negative feelings about OCF.